2017
DOI: 10.1021/acsnano.7b00796
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure and Dynamics of Single Platinum Atom Interactions with Monolayer MoS2

Abstract: We have studied atomic level interactions between single Pt atoms and the surface of monolayer MoS 2 using aberration-corrected annular dark field scanning transmission electron microscopy at an accelerating voltage of 60 kV. Strong contrast from single Pt atoms on the atomically resolved monolayer MoS 2 lattice enables their exact position to be determined with respect to the MoS 2 lattice, revealing stable binding sites. In regions of MoS 2 free from surface contamination, the Pt atoms are localized in S vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
140
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 45 publications
(60 reference statements)
1
140
0
Order By: Relevance
“…In addition to cation vacancies, anion vacancies of metal oxides,[19b,59] metal sulfides,[14a,60] metal nitrides[14b,61] can be well anchor sites to stabilize isolated metal atoms. Oxygen vacancy is considered as the most common defects in metal oxides, and its formation energy has great effects on the redox performance of metal oxides.…”
Section: Defects‐based Single Atomic Electrocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cation vacancies, anion vacancies of metal oxides,[19b,59] metal sulfides,[14a,60] metal nitrides[14b,61] can be well anchor sites to stabilize isolated metal atoms. Oxygen vacancy is considered as the most common defects in metal oxides, and its formation energy has great effects on the redox performance of metal oxides.…”
Section: Defects‐based Single Atomic Electrocatalystmentioning
confidence: 99%
“…When compared with traditionally prepared CoMoS 2 catalysts, MoS 2 monolayer sheets attached by single Co atoms have exhibited superior activity, stability, and selectivity without sulfur loss and deactivation. Recently, Li et al reported that the Pt single‐atom sites were anchored on monolayer MoS 2 through bond connections with S vacancies . The exact position of Pt could be determined at the MoS 2 lattice by the strong contrast between single Pt atoms and MoS 2 at the atomic level, which indicated the stable binding sites.…”
Section: Defects‐based Single Atomic Electrocatalystmentioning
confidence: 99%
“…S vacancies, which often appear in metal dichalcogenides, can also serve as anchoring sites to bound single metal atoms. By using aberration‐corrected annular dark‐field scanning transmission electron microscopy, Li et al revealed that isolated Pt atoms on defective MoS 2 were stabilized by bonding within S vacancies ( Figure ) . It was found by Liu et al that S vacancies can trap single Co metal atoms on S‐deficient MoS 2…”
Section: Unique Characteristics Of Single Metal Atom Catalystsmentioning
confidence: 99%
“…d) DFT relaxed atomic model showing a Pt atom in a 2S vacancy site. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Unique Characteristics Of Single Metal Atom Catalystsmentioning
confidence: 99%
See 1 more Smart Citation